Efektivitas Kebijakan Hukum Mengenai Penyelesaian Konflik Pertambangan Antara Kebijakan Pemerintah Pusat dan Daerah - Nur Aulia, Widi; Abdullah Faqih, Muhammad; Mulyadi, Dedi; Mulyana, Aji (Indonesian Journal of Public Administration Review, 2025)
The authority conflict between central and local governments in the mining sector presents a critical challenge within the framework of regional autonomy in Indonesia. This study aims to analyze the legal policy effectiveness in resolving such conflicts, with a specific focus on the mining sector in Southeast Sulawesi. The research employs a normative juridical approach, analyzing statutory regulations, legal doctrines, and a concrete case study. The findings reveal that the withdrawal of licensing authority by the central government through the enactment of Law No. 3 of 2020 has triggered structural tensions, legal uncertainty, investment barriers, and weak environmental oversight. The absence of an effective institutional mediation mechanism further exacerbates the conflict. The study recommends the establishment of an independent authority conflict resolution body and the strengthening of intergovernmental coordination through legal collaboration and good governance principles. A restructuring of central-local authority relations is essential to ensure a fair, effective, and adaptive decentralization policy for strategic sectors